تركيز الانتباه وعلاقته بالضربة الخلفية لدى لاعبي التنس المبتدئين - ابراهيم, قاسم; بجبوج, فؤاد; حاتم, رضا (Latakia University Journal -Medical Sciences Series, 2018)
The aim of the research was to identify the relationship between the concentration of attention and the level of the performance of backhand at thenovice tennis players. The researcher used the descriptive approach in the relational method of a sample of 24 tennis players and measured their focus by using the tachycop test and measuring their backhand performance using a test (Hensley) The study found a positive correlation between the concentration of attention and the level of performance of the backhandatnovice tennis players. هدف البحث الى التعرف على العلاقة بين تركيز الانتباه ومستوى اداء الضربة الخلفية لدى لاعبي التنس المبتدئيين.إذ استخدم الباحث المنهج الوصفي بأسلوب العلاقات الارتباطية لعينة مكونة من 24 لاعب مبتدئ برياضة التنس الأرضي حيث قام الباحث بقياس تركيز الانتباه باستخدام اختبار التختاسكوب وقياس مستوى أدائهم بالضربة الخلفية باستخدام اختبار (هنسلي ) وقد توصلت الدراسة الى وجود علاقة ارتباط معنوية موجبة بين درجة تركيز الانتباه ومستوى اداء الضربة الخلفية لدى لاعبي التنس المبتدئين .